SUPPLY CHAIN MANAGEMENT ETHICS: ANALYZE THE BUSINESS - Nurbasari, Anny; Adiprimadana Sanjaya, Fanlia; Khaidarmansyah, Khaidarmansyah; Maulamin, Taufan; thaib, Muprihan; Hendri, Edduar; Yuli Sugiarti, Diyah; septarina, Linda; Fetrimen, Fetrimen; Rismita, Rismita; Kosasih, Kosasih (International Journal of Supply Chain Management, 2020)
Abstract- The purpose of this paper is to describe a conceptual framework of Supply Chain Management Ethics (SCM-ethics). In any organization and related business, it is very important to understand the need for business ethics and examine the moral and ethical values of the flow of business work. It can be said that business ethics is the pillar for every business and organization because whenever the industry for business is communicating with their clients, employees and related people. The ethics and the social image of the organization will be in the focus for all the, directly and indirectly, persons who are part of the organization or activities as well as passively contributing in the growth of organization. Government has already established law and regulations for every trade now it is is the duty of any business for an organization to follow these rules and guidelines to maintain the dignity and trust of all towards the business. There are many factors which are directly related to business ethics such as increasing product price employee salary commitment to other parties and fulfillment of orders. The business manager is the most important person who has the responsibility to maintain the ethical status of the business. Time by time the norms and meaning of business ethics our changing. The philosophy e of every business and its ethics determines the base purpose of company e and also so helpful to obtain and improve the aims of the business. Ethics can be defined as an indirect protocol for rules which govern the business decision on daily e for periodical basis. For this purpose, the basic key terms are finance, finance paradigm, business issues, Human resource Management trade unions common Management strategy, sales, and marketing, emerging issues, production, property, modern history of property rights, slaves as property e, nature versus social construct, intellectual property and many more.